Liquid Nitrogen-Recycled Autograft Augmented with a Non-Vascularized Fibular Strut for Refractory Pediatric Osteosarcoma: A Case Report of the Cryo-Immunological Reconstruction - Mujjadid Idulhaq; Khrisna Purwa Satyaksa; Rachmad Faisal (HM Publisher, 2025)
Reconstruction of large segmental bone defects following limb salvage surgery for osteosarcoma presents a significant challenge in pediatric populations, particularly in resource-limited settings where expandable endoprostheses are inaccessible. This study evaluates the efficacy of a biological reconstruction technique using Liquid Nitrogen-treated recycled autograft augmented with a fibular strut, known as the Modified Capanna Technique. We present the case of an 8-year-old female with Enneking Stage IIB high-grade osteoblastic osteosarcoma of the distal femur. The patient exhibited a refractory response (Huvos Grade II) to a neoadjuvant non-methotrexate chemotherapy regimen. Wide resection was performed, followed by a specific cryo-protocol: the tumor-bearing bone was frozen in Liquid Nitrogen (−196°C) for 20 minutes, thawed physiologically, augmented with an intramedullary non-vascularized fibular strut, and stabilized with a locking compression plate. At 12 months postoperative, the patient achieved solid radiographic union with a Radiographic Union Scale for Tibial fractures score of 11/12. No local recurrence or distant metastasis was detected. The Musculoskeletal Tumor Society score improved from 10% pre-operatively to 80% post-operatively, reflecting independent ambulation. A comparative analysis revealed that the procedure cost was approximately 12% of a standard imported megaprosthesis. In conclusion, the liquid nitrogen-recycled autograft, when mechanically augmented, offers a theoretically sound and cost-effective limb salvage solution. It provides immediate anatomical restoration and potential cryo-immunological benefits, making it a viable alternative for refractory cases in developing healthcare systems.